A CRITICAL ASSESSMENT OF RETAIL SHOPPING MALLS IN TURKEY THROUGH LEGISLATIVE FRAMEWORKS - Ceylan, Rumeysa; Ozbakir, Buket Aysegul; Erol, Isil (MIDDLE EAST TECHNICAL UNIV, 2017)
Location decision and standards of shopping malls keep relevancy at a standstill position in the planning agenda of Turkey when considered the increasing numbers of construction even though the economic crisis in the World. By the end of June 2014, the number of shopping malls has reached to 412 (including under construction) and the total gross leasable area to 10.8 million m(2) (AARREC, 2015). While there are many regulations and planning legislative frameworks related to the classification and standards of shopping malls around the world, such development has just began to form in Turkey. Although some regulations for planning the retail spaces have existed since the 1960s, many of them lacked both international standards and a national classification schema that fits for Turkey's unique market demands. This research attempts to fulfill a part in understanding the historical journey of shopping malls in Turkey with reference to the cases of Europe, Asia and America. The literature review aims to explore the variations in standards and classification schemas among different geographies in time. Based on the literature review, secondly, the research aims to shed light on the current legislative framework in Turkey with regard to planning, design and classification of shopping malls. To this end; three laws and seven regulations have been analyzed through a set of six parameters derived from literature review. These parameters are: definitions and standards, location decisions, protection of ecological environment, transportation and parking, hierarchy between the plans and legend categories of plans. Results indicate that recent legislative framework of Turkey cannot fully address a unique, sustainable and national classification schema for shopping malls. The framework also fail in defining the location decision parameters. Whilst, the new law for shopping malls attempts to regulate and address the need for parking lots comprehensively. On the other hand the same law neglects the hierarchy of plans and needs to be improved.
Keywords: Retail Spaces; Shopping Malls; Legislative; Classification and Definitions; Architecture